Desipramine, commonly used as a noradrenergic neuroprotectant in 6-OHDA-lesions, leads to local functional changes in the urinary bladder and gastrointestinal tract in healthy rats. Issue 11 (November 2020) - Murillo, Maria del Pilar; Aronsson, Patrik; Winder, Michael; Carlsson, Thomas
Abstract: The 6-hydroxydopamine (6-OHDA) rat model is one of the most common animal models of Parkinson's disease. When experimentally inducing dopaminergic neurodegeneration in the nigrostriatal pathway using 6-OHDA, the noradrenergic reuptake inhibitor desipramine is often systemically injected in order to protect against damages to the noradrenergic system in the brain. An increasing number of studies are focusing on understanding the pathophysiological changes underlying autonomic non-motor symptoms, in particular urinary bladder and gastrointestinal dysfunctions, of the disease. Several of these studies have investigated the contractile properties and the activation of smooth muscle in the 6-OHDA rat model. Since the injection of desipramine is commonly placed in close proximity to the urinary bladder and gastrointestinal tract, in the current study we wanted to understand if the drug alone has an effect. For this, we have injected a single dose (25 mg/kg) of desipramine either intraperitonially or subcutaneously and investigated smooth muscle contractility in vitro in the urinary bladder, proximal colon and distal ileum four weeks post injection. Our data show that desipramine significantly alters smooth muscle contractility of the urinary bladder and proximal colon in healthy rats. Conclusively, we suggest, based on our data, that desipramine should be omitted when using the 6-OHDA rat model to investigate smooth muscle function in Parkinson's disease research. Abstract : Parkinson's disease; Non-motor symptoms; Urinary bladder detrusor; Colon; Ileum; Gastrointestinal system; Physiology; Neurology; Pharmacology; Urology.